High-dimensional immune profiling of follicular fluid and systemic circulation reveals distinct immune signatures in women with polycystic ovary syndrome - Banerjee, Soma; Jaimes, Fernanda L.; Mohamed, Mona A.; Zettel, Abigail; Graupe, Nesya G.; Cooney, Laura G.; Stanic, Aleksandar K. (Frontiers in Immunology, 2025)
BackgroundPersistent low-grade inflammation has been hypothesized as a possible key contributor to polycystic ovary syndrome pathophysiology through associative studies. Since immune cells within the ovarian follicle—the central site of PCOS dysfunction—play pivotal roles in immune defense and regulation of ovulation, establishing a definitive cellular map of normal and PCOS-affected follicular immune composition is essential.MethodThis is a prospective cohort study of women with PCOS (Rotterdam criteria) and controls undergoing in vitro fertilization (IVF). Peripheral blood was collected before treatment (visit 1) and again at transvaginal oocyte retrieval (TVOR, visit 2). Follicular fluid (FF) was obtained from the first two dominant follicles during TVOR. We measured the cytokines and angiogenic factors in both plasma and FF using multiplexed cytometric bead assays. The cellular immune composition was evaluated by using high-dimensional multispectral flow cytometry, followed by dimensionality reduction and graph-based clustering analyses.ResultsWe found that the TVOR plasma contained significantly higher concentrations of IL-2, IL-4, IL-9, IL-17A, TNF-α, and MCP-1 compared to the follicular fluid, whereas the follicular fluid was enriched with angiogenic factors such as VEGF and EGF. Notably, pre-treatment plasma samples from PCOS patients showed elevated Il-4, IL-6, IL-9, and IL-10, which were partially resolved by TVOR. Moreover, the PCOS follicular fluid exhibited higher numbers of classical monocytes and a trend toward increased CTLA4-positive T regulatory cells relative to the controls.ConclusionOur findings highlight a compartment-specific immunome in PCOS, marked by distinct cytokine and angiogenic factor distributions in circulation versus follicular fluid. PCOS was characterized by elevated systemic inflammatory markers before treatment, which were partially normalized by TVOR, yet key immune differences persisted at the follicular level. These results underscore the utility of comprehensive multiparametric analyses—including high-dimensional flow cytometry—to uncover immune dysregulation and identify potential therapeutic targets in PCOS.